2019
DOI: 10.3899/jrheum.180972
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use in Patients with Ankylosing Spondylitis Is Common in the United States: Outcomes of a Retrospective Cohort Study

Abstract: Objective.To assess the prevalence of chronic opioid use in patients with ankylosing spondylitis (AS), and to compare the characteristics of patients with and without chronic opioid use.Methods.This was a retrospective cohort study of patients with AS identified in the Truven Health MarketScan Research database between January 1, 2012, and March 31, 2017. Commercial and Medicaid claims data were examined using both specific (720.0 and M45.x) and broader (720.x and M45.x) International Classification of Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…This study demonstrates that long-term prescription opioid use, as well as any opioid use, immediate-acting, extended-acting and > 3 types of opioid prescriptions were all highest among patients with AS. Long-term prescription opioid use was prevalent in 25% of patients with AS which is consistent with findings published in a recent study of 11 945 patients with AS identified by ICD-9 codes in Truven Marketscan commercial claims where 23.5% patients had chronic opioid use 32. One possible explanation for the high prevalence of long-term opioid use in AS is that chronic low back pain, which is associated with opioid prescription33–35, is more common among patients with AS and more debilitating than pain in other locations.…”
Section: Discussionsupporting
confidence: 89%
“…This study demonstrates that long-term prescription opioid use, as well as any opioid use, immediate-acting, extended-acting and > 3 types of opioid prescriptions were all highest among patients with AS. Long-term prescription opioid use was prevalent in 25% of patients with AS which is consistent with findings published in a recent study of 11 945 patients with AS identified by ICD-9 codes in Truven Marketscan commercial claims where 23.5% patients had chronic opioid use 32. One possible explanation for the high prevalence of long-term opioid use in AS is that chronic low back pain, which is associated with opioid prescription33–35, is more common among patients with AS and more debilitating than pain in other locations.…”
Section: Discussionsupporting
confidence: 89%
“…Patients often seek consultations with various types of healthcare providers in their journey toward diagnosis [25], undergoing expensive, unnecessary diagnostic workup and inappropriate medical interventions that may not directly improve patient outcomes [25,44,45 ▪ ] For example, an increase in opioid use was reported in patients with ankylosing spondylitis, representing a suboptimal treatment with economic ramifications to the health system [46]. Thus, a timely diagnosis of axSpA can yield substantial cost savings and increase resource efficiency among payers, physicians, and patients [47].…”
Section: Opportunities and Potential Benefits With Machine Learning Imentioning
confidence: 99%
“…One‐fifth of studies included only opioid‐naïve individuals (29 studies), mostly defined as the absence of opioid use in the 6 24,36,37,52,65,69–73 or 12 months 30,48,61,62,74–83 prior to the index date. Some studies investigated opioid use among patients with various specific health conditions: 43 studies 24,26–28,31,37,43,48,49,51,52,59,62,65,70,74,77–80,82–104 focused on noncancer pain, 14 studies 55,56,64,69,105–114 on musculoskeletal conditions, 13 studies 38–40,57,81,115–122 on injuries or trauma and eight studies 23,32,53,67,75,123–125 on infectious diseases. Seven studies 41,44,45,71,126–128 included patients with both cancer and noncancer pain, and six studies evaluated patients with cancer 60,129,130 or cancer survivors 61,131,132 .…”
Section: Resultsmentioning
confidence: 99%